2017
DOI: 10.1515/picbe-2017-0055
|View full text |Cite
|
Sign up to set email alerts
|

The role of international competences in increasing graduates’ access to the labor market

Abstract: (Stan, Butum & Zodieru, 2016)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…The demand for specialized competencies and skills regarding practical activities is now rising, causing the competitiveness in a labor market that relates to employability rates [5,21]. Prior studies have reported their effort in statistically computing the predictive power of practical activities on KSC or/and employability [5,6,22]. For example, Gora et al [6] reported the significant relationship between practical activities and KSC while failed to prove a substantial relationship between practical activities and employability.…”
Section: Practical Activitiesmentioning
confidence: 99%
“…The demand for specialized competencies and skills regarding practical activities is now rising, causing the competitiveness in a labor market that relates to employability rates [5,21]. Prior studies have reported their effort in statistically computing the predictive power of practical activities on KSC or/and employability [5,6,22]. For example, Gora et al [6] reported the significant relationship between practical activities and KSC while failed to prove a substantial relationship between practical activities and employability.…”
Section: Practical Activitiesmentioning
confidence: 99%
“…Starting from the idea that there is a link between the quality of the educational process and the skills acquired by the students, studies [6] show that there is also a connection between the curriculum, the international competencies and the chances in employment in the labor market.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…As far as practical activities are concerned, they play an important role in the student education process [47]. The study conducted by Butum [6], regarding students' perceptions of university performance in both Europe and Romania, illustrates that they most appreciate the professional competences they acquire over their years of study, practical activities, and the possibility of having access to international training programs. As already mentioned, teachers have a significant role in the development of students' competencies.…”
Section: Hypothesis 4 (H4)mentioning
confidence: 99%
See 2 more Smart Citations